The Implications of Daylight Saving Time: A Field Experiment on Cognitive Performance and Risk Taking - Markus Schaffner; Jayanta Sarkar; Benno Torgler; Uwe Dulleck (Center for Research in Economics, Management and the Arts (CREMA), 2015)
To explore the effects of daylights saving time (DST) transition on cognitive performance and risk-taking behaviour immediately before and one week after the shift to DST, this study examines two Australian populations living in similar geographic surroundings who experience either no DST transition (Queensland) or a one-hour DST desynchronization (New South Wales). This exogenous variation creates natural control (QLD) and treatment (NSW) groups that enable isolation and identification of the DST transition's effect on the two outcome variables. Proximity to the border ensures similar socio-demographic and socio-economic conditions and thus permits comparison of the cognitive performance and risk-taking behaviour of affected versus unaffected individuals. The results suggest that exposure to the DST transition has no significant impact on either cognitive performance or risk-taking behaviour.
Keywords: D81; C93; C21; I1; 330; Daylight Saving Time; Risk-Taking Behaviour; Cognitive Performance; Field Experiment